Assessment of Toxoplasma Seropositivity in Children Suffering from Attention Deficit Hyperactivity Disorder: - Khosravi, Mohammad Hossein; Afsharpaiman, Shahla; Faridchehr, Mahdi; Komijani, Mojtaba; Radfar, Shokoofeh; Amirsalari, Susan; Torkaman, Mohammad; Shirbazoo, Shahnaz (Galen Medical Journal, 2016)
Background: Toxoplasmosis, a protozoan infection caused by Toxoplasma gondii, is suggested to be a risk factor for many psychological disorders such as schizophrenia and depression. Attention deficit hyperactivity disorder (ADHD) is one of the most common psychiatric disorders among children. Previous studies have assessed the correlation between ADHD and infectious diseases like toxoplasmosis. So we aimed to investigate the possible correlation between Toxoplasma seropositivity and ADHD in children. Materials and Methods: In this cross-sectional study children with signs of ADHD were regarded as patients and underwent clinical assessments. Diagnosis of these patients was based on DSM-IV-TR system which was performed by a pediatric psychiatrist. Forty-eight Children without signs of ADHD or other psychic disorders were considered as control, and 48 patients were considered as case group. Parents were asked to answer a questionnaire including demographic, pregnancy and habitual questions. Blood samples were taken from all individuals and assessed for anti-Toxoplasma IgM and IgG antibodies. Results: Ninety-six male and female patients with a mean age of 8.12 years underwent analysis. Seropositivity rate for anti-T.gondii IgG antibody was 4.2% in the case and 2.1% in control individuals (P=0.92). Anti-T.gondii IgM antibodies were not found in control individuals while it was found in 2.1% of case individuals (P=0.74). There was no statistically significant association between seroprevalence of IgM (P=0.74) and IgG (P=0.92) antibodies and ADHD in study individuals. Conclusion: Our findings showed that the toxoplasmosis seropositivity has no significant difference between children with and without ADHD. Further studies are needed with a larger amount of individuals. [GMJ. 2016;5(4):188-93]